Structure of scientific knowledge flows to intergovernmental organizations - Kimitaka Asatani; Yurie Iwata; Yuta Tomokiyo; Basil Mahfouz; Masaru Yarime; Ichiro Sakata (Proceedings of the National Academy of Sciences, 2026)
Intergovernmental organizations (IGOs) attempt to shape global policy through scientific guidelines and assessments. While they rely on external scientists to bridge research and IGO advisory processes, the structural pathways connecting science to IGO documents remain unexamined. By linking 230,737 scientific papers referenced in IGO documents (2015–2023) to their authors and coauthorship networks across 23 research fields, we identified a small cohort of “Highly IGO-Cited Scientists” (HIC-Sci)—typically comprising 0.7% to 4.4% of authors whose work accounts for 30% of IGO-cited papers. This structural concentration is associated with relational and cognitive patterns: dense transnational collaboration networks, overlapping memberships on advisory bodies such as the Intergovernmental Panel on Climate Change, rapid uptake in IGO documents, and standardized policy-oriented vocabularies. Geographically, HIC-Sci networks follow a core–periphery structure centered on Western Europe. Established fields, such as climate modeling, show stronger concentration, whereas emerging domains such as data science & AI show more distributed citation patterns. Major IGOs frequently cocite the same HIC-Sci papers, compounding this concentration through synchronized diffusion across IGOs. This concentration persists despite IGOs’ efforts to broaden participation and diversify their evidence base. While IGOs have developed criteria for selecting knowledge in advance, our framework provides a basis for subsequent assessment of how IGOs’ efforts to influence policy rely on a concentrated set of HIC-Sci.